Signifiance and transubstantiation: Julia Kristeva and originary translation (Colloquia Comparativa Litterarum, 2025)
The article reconstructs the evolution of Kristeva’s major term signifiance in her endeavour to conceptualise literature and art as processes translating the continuous making and unmaking of the subject. This evolution involves the shift from Kristeva’s early focus predominantly on poetry towards her later emphasis on the novel (Proust and Colette), which led her to the concept of transubstantiation as “metaphore become flesh”.
Keywords: artistic avant-garde; semiotic; signifiance; transubstantiation